Market Microstructure and Stock Return Predictions - Huang, Roger D.; Stoll, Hans R. (Review of Financial Studies, 1994)
To what extent are the empirical regularities implied by market microstructure theories useful in predicting the short-run behavior of stock returns? A two-equation econometric model of quote revisions and transaction returns is developed and used to identify the relative importance of different microstructure theories and to make predictions. Microstructure variables and lagged stock index futures returns have in-sample and out-of-sample predictive power based on data observed at five-minute intervals. The most striking microstructure implication of the model, confirmed by the empirical results, specifies that the expected quote return is positively related to the deviation between the transaction price and the quote midpoint while the expected transaction return is negatively related to the same variable.